2005
DOI: 10.1080/15287390590925465
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrospermopsin Genotoxicity and Cytotoxicity: Role Of Cytochrome P-450 and Oxidative Stress

Abstract: Cylindrospermopsin (CYN) is a cyanobacterial toxin found in drinking-water sources world wide. It was the likely cause of human poisonings in Australia and possibly Brazil. Although CYN itself is a potent protein synthesis inhibitor, its acute toxicity appears to be mediated by cytochrome p-450 (CYP450)-generated metabolites. CYN also induces genotoxic effects both in vitro and in vivo, and preliminary evidence suggests that tumors are generated by oral exposure to CYN. To understand the role of CYP450-activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
149
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(165 citation statements)
references
References 28 publications
15
149
0
1
Order By: Relevance
“…Most studies concerning the cytotoxic/genotoxic influence of CYN was conducted with liver cells or hepatoma cell lines as CYN is known to be a hepatotoxin. These studies confirmed that the toxin is able to induce genotoxic damage, such as DNA strand breaks, the increase in the micronuclei number, nuclear buds and nuclear bridges [15,[33][34][35]. Similar effects were also observed in other metabolically active cells, e.g.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Most studies concerning the cytotoxic/genotoxic influence of CYN was conducted with liver cells or hepatoma cell lines as CYN is known to be a hepatotoxin. These studies confirmed that the toxin is able to induce genotoxic damage, such as DNA strand breaks, the increase in the micronuclei number, nuclear buds and nuclear bridges [15,[33][34][35]. Similar effects were also observed in other metabolically active cells, e.g.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly to MCs, the main target for CYN is the liver. The studies on CYN genotoxic potential revealed that the toxin is also responsible for DNA damage in hepatocytes [15]. Recently, the toxin-induced formation of DNA single-strand breaks, increase in the frequency of micronuclei and nuclear buds in human peripheral blood lymphocytes exposed to CYN were reported [16].…”
Section: Introductionmentioning
confidence: 99%
“…Extraction and purification of pure cylindrospermopsin was undertaken as previously described by Humpage et al (2005).…”
Section: Extraction and Purification Of Cylindrospermopsinmentioning
confidence: 99%
“…Esta técnica permite providenciar uma informação quantitativa e qualitativa, contudo, para tal análise são necessários padrões da toxina purificada, os quais por vezes são difíceis de serem obtidos, além de necessitar de grandes volumes de amostra quando a toxina se encontra em baixas concentrações, e de passos para purificação das amostras (RIVASSEAU et al, 1999;RAPALA et al, 2002;MATHYS;SURHOLT, 2004;SANGOLKAR;MASKE;CHAKRABARTI, 2006;. A cromatografia líquida acoplada à espectrometria de massas (LC-MS) e a LC-MS/MS também são métodos muito difundidos que fornecem resultados mais precisos sobre a presença desta toxina, bem como disponibilizam dados referentes aos picos gerados pela ionização e fragmentação da molécula (CHISWELL et al, 1999;FALCONER et al, 1999;LI et al, 2001a;LI et al, 2001b;FASTNER et al, 2003;HUMPAGE et al, 2005;FROSCIO et al, 2008;RASMUSSEN et al, 2008;YLMAZ et al, 2008;BLÁHOVÁ et al, 2009;GALLO et al, 2009;PREUβEL et al, 2009;MAZMOUZ et al, 2010;MEREL et al, 2010;ANTAL et al, 2011;BALLOT et al, 2011;EVERSON et al, 2011;MAZMOUZ et al, 2011;Mc GREGOR et al, 2011). IV) Utilizar os dados gerados no sequenciamento gênomico das duas linhagens para mapeamentos e buscas por genes relacionados à síntese de metabólitos secundários, com foco principal na CYN e genes relacionados à fixação biológica do N 2 e diferenciação dos heterócitos.…”
Section: Métodos De Detecção De Cynunclassified